1990
DOI: 10.1128/mcb.10.11.5991
|View full text |Cite
|
Sign up to set email alerts
|

Fine-structure mutational analysis of a stage- and tissue-specific promoter element of the Drosophila glue gene Sgs-3.

Abstract: The Sgs-3 gene of Drosophila melanogaster exhibits a tightly regulated pattern of expression governed by two functionally equivalent elements within 1 kb of the gene, each of which is sufficient to confer third-instar salivary gland-specific transcription. In this report we describe a detailed functional analysis of one of these, the proximal element. To determine the nucleotides responsible for specific expression, we have introduced mutations into the proximal element and then assessed the effects of each al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…In all cases, the region of homology is located within sequences required for correct expression of the adjacent glue gene (19, 51, 57; this work). The most striking evidence for a regulatory function of conserved sequences in the upstream region of glue genes comes from the work of Todo et al (55); they first show which single base pairs in the proximal element of Sgs-3 are absolutely required for correct function and then find these base pairs to be located among conserved sequence regions 5' of all sequenced glue genes. Todo et al (55) found that a functional Sgs-3 regulatory element contains a TNTTTG homology and a TCCAT(T/A) homology separated by a certain number of nucleotides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, the region of homology is located within sequences required for correct expression of the adjacent glue gene (19, 51, 57; this work). The most striking evidence for a regulatory function of conserved sequences in the upstream region of glue genes comes from the work of Todo et al (55); they first show which single base pairs in the proximal element of Sgs-3 are absolutely required for correct function and then find these base pairs to be located among conserved sequence regions 5' of all sequenced glue genes. Todo et al (55) found that a functional Sgs-3 regulatory element contains a TNTTTG homology and a TCCAT(T/A) homology separated by a certain number of nucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…The most striking evidence for a regulatory function of conserved sequences in the upstream region of glue genes comes from the work of Todo et al (55); they first show which single base pairs in the proximal element of Sgs-3 are absolutely required for correct function and then find these base pairs to be located among conserved sequence regions 5' of all sequenced glue genes. Todo et al (55) found that a functional Sgs-3 regulatory element contains a TNTTTG homology and a TCCAT(T/A) homology separated by a certain number of nucleotides. There are two of these elements located in the 86-bp cis-acting region of Sgs-71Sgs-8 described in this work in an interspersed array facing We know that at least the one closer to Sgs-7 is necessary for correct expression of …”
Section: Resultsmentioning
confidence: 99%
“…Reference Eveleth et al 1986 This study Todo et al 1990 McGinnis et al 1986 Todo et al 1990 Mestril et al 1986 Weiher et al 1983 FIG. 1.…”
Section: Hsp-22 5 ' -Atggaai-2 -G a C C T T C -~~~mentioning
confidence: 94%
“…Cis-acting regulatory elements may be as small as 6-14 bp (Berg and yon Hipple 1988; Karim et al 1990;Todo et al 1990). The interplay of a myriad oftrans-acting factors with an ensemble of cis-acting motifs is required for the appropriate regulation of eukaryotic genes (Jantzen et al 1987;Lichtsteiner et al 1987;Bell et al 1988;Read et al 1990).…”
Section: Conserved Sequence Elements In the 5' Region Of The Drosophimentioning
confidence: 99%